Molecular diagnosis of Leishmania spp. in dogs of a subtropical locality of Argentina - Ascencio, Mariano; Sarmiento, Nestor Fabian; Schnittger, Leonhard; Florin-Christensen, Mónica; Rodriguez, Anabel Elisa (Wiley, 2020)
Leishmaniosis is a tropical and subtropical vector‐borne disease caused by hemoparasites of the genus Leishmania. The disease can infect humans, as well as domestic and wildlife animals. Dogs are the main reservoir for L. infantum, the aetiological agent of visceral leishmaniosis (VL) in America, and a domestic source of L. braziliensis, the most widespread aetiological agent of American tegumentary leishmaniosis. Infected dogs can develop a clinical syndrome called canine leishmaniosis (CanL), which presents with skin lesions, mild fever; additionally hepatomegaly and splenomegaly can be observed, although asymptomatic infections are frequent. Direct microscopic observation of the parasite in bone marrow, blood, skin scrapings and conjunctival swab samples is the gold standard of diagnosis and is usually complemented with serological tests, and to a lesser extent, molecular detection of the parasite. In Argentina, leishmaniosis is an emerging disease, with a growing number of human and canine clinical cases since 2006. Our study was carried out in Mercedes, a town located in the subtropical north‐eastern area of Argentina, where dogs with positive parasitological test results for Leishmania spp. must be euthanized according to local regulations. We evaluated the presence of Leishmania spp. DNA in the blood of dogs (n = 166) from urban and peri‐urban zones. Genomic DNA was extracted from whole blood using Chelex 100 resin and a conserved 116 bp region of the kinetoplastid DNA was amplified by conventional PCR. Clinical signs, age and gender were recorded. Our results showed that 120 out of 166 surveyed dogs (72%) were positive for Leishmania spp. DNA of which only seven were positive by parasitological and serological tests. No significant correlation between positive cases and gender or age groups was found. This report shows the high prevalence of this disease in Argentina and contributes to improve public health policy with regard to diagnosis, prevention and treatment of infected dogs.